Relation of Transversus Abdominis to Rectus Abdominis Muscle in Various Anatomical Landmark Levels: A Cadaveric Study - Totsapol Surichamorn; Thiti Tantitham (Archives of Plastic Surgery)
Background Posterior Component Separation (PCS) is a surgical technique used in abdominal wall reconstruction. Understanding the relationship between the rectus abdominis and transversus abdominis muscles and the location of intercostal nerves is crucial for minimizing nerve injury during PCS. This cadaveric study aimed to investigate these anatomical relationships and propose practical guidelines for safer PCS procedures.